The Effect of Product Quality and Price with The Halal Label as a Moderating Variable on Purchasing Decisions Zoya Halal Cosmetics in Pekanbaru City - Isnania, Masita; Wasnuri, Rendra; Marhadi, Marhadi (International Journal of Economic, Business & Applications, 2022)
The purpose of this study is to determine the effect of product quality and price on purchase decisions for Zoya brand halal cosmetics in Pekanbaru, using halal labels as a moderating variable. The population in this study are consumers who have purchased and used Zoya cosmetics and are domiciled in the city of Pekanbaru. The sampling technique is non-probability sampling, with a total sample of 128 respondents. This study uses structural equation modeling with partial least squares (SEM-PLS) in analyzing the data. The results showed that product quality had a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchase decisions. As a moderating variable, the halal label strengthens the positive relationship between product quality and purchase decisions. Furthermore, the halal label acts as a moderator, weakening the negative relationship between price and purchase decision